From the Library Review Perspectives: Strategies to Instill Efficient Character Education Values in Indonesian EFL Learning Dynamics - Wijaya, Kristian Florensio (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2024)
There should be a decent complementary element to equalize the proficiency-based learning activities attempting to breed skilled, innovative, and knowledgeable target language academicians. Following this belief, professional second language educators should incessantly transmit various kinds of efficient character education values in their daily classroom learning routines as learners begin to showcase more promising and positive learning behaviors in sustaining the continuity of language exposure. This current small-scale library study was enacted to profoundly investigate the possible pedagogical strategies second-language educationalists can internalize to holistically infuse more meaningful character education values in Indonesian EFL learning dynamics. To fulfill this study objective, the researcher employed a thematic analysis approach in this current small-scale library investigation to systematically cluster the most identical research results into some relatable themes. Accordingly, 20 prior character education studies ranging from 2018 to 2022 year were selected to produce more reliable robust findings. From the thematically categorized research results, the perfect embodiment of efficient character education values was ascertained when Indonesian EFL teachers are willing to play roles as supportive learning facilitators and implement variegated teaching strategies in their regular classroom learning dynamics. Some future recommendations were also depicted for the constant advancement of this educational research field.